(untitled) (Journal of the College of Basic Education, 2022)
To study the dialectThe differences in the dialects between the Arab tribes were clear, and could be noticed by a book studentThe Arabic language, which is specialized in it, there were differences between the dialect of Mecca and the dialects of the desert, and between thesethe last one with each other) (1), so the student in this field has the right to monitor these differences between the Arabic dialects,Especially within the subject of the study, and to show these differences separately, it was necessary to divide the roleDialectism is divided into two main branches according to the levels (the morphological level and the phonetic level)., And fromInclusion of dialectical phenomena within each level and discussing them in detail.